Core curriculum online lecture series in musculoskeletal imaging: initial results - White, Lawrence M.; Rubin, David A.; Pathria, Mini N.; Tuite, Michael J.; Recht, Michael P. (Skeletal radiology, 2020)
Objective To augment the educational resources available to training programs and trainees in musculoskeletal (MSK) radiology by creating a comprehensive series of Web-based open-access core curriculum lectures. Materials and methods Speakers with recognized content and lecturing expertise in MSK radiology were invited to create digitally recorded lecture presentations across a series of 42 core curriculum topics in MSK imaging. Resultant presentation recordings, organized under curriculum subject headings, were archived as open-access video file recordings for online viewing on a dedicated Web page ( http://radiologycorelectures.org/msk/ ). Information regarding the online core curriculum lecture series was distributed to members of the International Skeletal Society, Society of Skeletal Radiology, Society of Chairs of Academic Radiology Departments, and the Association of Program Directors in Radiology. Web page and online lecture utilization data were collected using Google Analytics (Alphabet, Mountain View, CA, USA). Results Forty-two lectures, by 38 speakers, were recorded, edited and hosted online. Lectures spanned ACGME curriculum categories of musculoskeletal trauma, arthritis, metabolic diseases, marrow, infection, tumors, imaging of internal derangement of joints, congenital disorders, and orthopedic imaging. Online access to the core curriculum lectures was opened on March 4, 2018. As of January 20, 2019, the core curriculum lectures have had 77,573 page views from 34,977 sessions. Conclusions To date, the MSK core curriculum lecture series lectures have been widely accessed and viewed. It is envisioned that the initial success of the project will serve to promote ongoing content renewal and expansion to the lecture materials over time.